#### Answer

y=-3

#### Work Step by Step

Simplifying
27 + -8(2 + -1y) = -13
27 + (2 * -8 + -1y * -8) = -13
27 + (-16 + 8y) = -13
Combine like terms: 27 + -16 = 11
11 + 8y = -13
Solving
11 + 8y = -13
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-11' to each side of the equation.
11 + -11 + 8y = -13 + -11
Combine like terms: 11 + -11 = 0
0 + 8y = -13 + -11
8y = -13 + -11
Combine like terms: -13 + -11 = -24
8y = -24
Divide each side by '8'.
y = -3
Simplifying
y = -3